Development of internal browning during low temperature storage of pineapple cv. 'Trad-Srithong' fruit harvested at different times of the day - Youryon, P.; Wongs-Aree, C.; McGlasson, W. B.; Glahan, S.; Kanlayanarat, S. (My University, 2011)
Pineapple plants cv. 'Trad-Srithong' (Ananas comosus L.) were found to exhibit crassulacean acid metabolism (CAM). The concentrations of organic acids were higher in mature crown and stem leaves harvested at 0600 than at 1200 h but there were no significant differences in acid concentrations among fruit harvested at these times. Fruit of 'Trad-Srithong' (Queen group) are highly sensitive to internal browning (IB), a form of chilling injury, when stored at <15 °C. Fruit were harvested at 0600 and 1200 h and stored at 8, 13 and 20 °C. IB developed in fruit stored at 8 and 13 °C after 10 days but no symptom developed in control fruit stored at 20 °C. Time of day, when the fruit were harvested had no effect on the development of IB in 'Trad-Srithong' fruit. TA increased in fruit during storage at all temperatures. Juice extracted from the pulp had higher TA and lower pH than the core tissue and symptoms of IB were more severe in the flesh surrounding the core. Ascorbic acid decreased late during storage period.
Keywords: Ananas comosus; Black heart; CAM plant; Fruit acidity; Harvesting time